Bluey. Seasons 1 & 2 [videorecording (DVD)] - Brumm, Joe (BBC Studios, 2022)
"Bluey is a loveable, inexhaustible little six-year-old Blue Heeler dog, who lives with her Mum, Dad and her four year old little sister, Bingo. Like every kid her age, the thing Bluey likes to do best is play games that unfold in unpredictable and hilarious ways, bringing her family and the whole neighborhood into her world of fun"--container.